Development of sulfonated carbon-based catalysts from glycerol and cow dung for biodiesel production from high free fatty acid oils - Sangar, Shatesh Kumar (2020)
In this research, cost efficient and environmental friendly sulfonated carbon-based catalyst was prepared from glycerol (CG) and cow dung (CD) and subsequently functionalized with concentrated sulfuric acid (H2SO4) at different sulfonation time. The physico-chemical properties of the prepared catalysts were characterized by using X-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), temperature programmed desorption-ammonia (TPD-NH3), Thermogravimetric analysis (TGA), Brunauer–Emmett–Teller (BET) surface area, variable pressure scanning electron microscope (VPSEM), high resolution transmission electron microscopy (HR-TEM), X-ray Fluorescene (XRF) analysis and CHNSO elemental analysis. The carbon that was sulfonated with H2SO4 for 10 h (SCG- (10) and SCD-(10) catalysts) were chosen to be used in optimization studies due to the synergistic effect of good physicochemical properties including high amount of acid sites and sulfur attached to carbon. The amount of sulfur and total acidity were increased significantly after being sulfonated at different time of reflux; whereas, the SCG-(10) and SCD-(10) catalysts showed the highest total amount of acidity 35117.14 μmol/g and 16653.49 μmol/g, respectively. The esterification of palm fatty acid distillate (PFAD) over SCG-(10) catalyst was optimized via the one-variable-at-a-time technique, and fatty acid methyl ester (FAME) of 97.8% was achieved at optimum conditions of 1 h reaction time, 90 °C reaction temperature, 5 wt% catalyst loading, and 18:1 methanol-to-oil molar ratio. The SCG-(10) catalyst was successfully reused for 7 cycles and it was found that the catalytic activity maintained with >96% of FAME yield for the first three run. The synthesized PFAD-derived biodiesel has complied with the international biodiesel standards of EN14214 and ASTM D6751. The amount of sulfur in biodiesel are lower than the maximum limit of ASTM D6751. Taguchi approach using four parameters at four-level, L-16 (44) of experiment design was employed to compare the experimental results. Reaction temperature was the most influenced control parameter on biodiesel production with high S/N ratio and F-value. The optimum conditions for the highest biodiesel production was at reaction temperature at level 4 (90 ℃), methanol to PFAD molar ratio at level 3 (18:1), catalyst loading at level 4 (6 wt. %) and reaction time at level 3 (1.5 h). As SCG-(10) catalyst showed super catalytic performance in esterification of PFAD, it also been used for simultaneous esterification-transesterification of waste cooking oil (WCO) and chicken fat oil (CFO). The methyl ester production from WCO and CFO were also successfully performed by using SCG-(10) catalyst and obtained FAME yield 92.3% (optimum conditions of 5 wt% catalyst loading with 22:1 methanol to WCO molar ratio for 3 h reaction time and 100 ℃ reaction temperature) and 90.8% (optimised conditions of 5 wt% catalyst loading with 18:1 methanol to CFO molar ratio for 1 h reaction time and 70 ℃ reaction temperature), respectively. In addition, SCD-(10) catalyst was used in esterification of PFAD and achieved high FFA conversion of 96.5% at optimum parameter of 18:1 methanol to PFAD molar ratio, 4wt% of catalyst loading and 90 °C reaction temperature within 1 h reaction time. SCD-(10) catalyst is capable to convert PFAD to biodiesel with FFA conversion >90% for 3 consecutive cycles. As a conclusion, both SCG-(10) and SCD-(10) catalysts can be easily recovered, impressive catalytic activity and efficient for biodiesel production with high reusability.